Language and Reality : Selected Writings of Sydney Lamb. - Lamb, Sydney (Open linguistics series., 2004)
Language and Reality presents selected writings of Professor Sydney M. Lamb, including six new works and several which have been re-worked for publication here. Although he is a leading figure in linguistic science, many of the papers are far from well known, some of them having appeared in more obscure venues of publication, and for the most part unavailable to the wider linguistic community. The book is divided into four parts, the first of which includes papers offering insight into the man behind this pioneering approach to doing linguistics that might best be summed up as?linguistics to.